Accreditation of municipalities to administer housing programmes: the decentralisation dilemma - Sithole, S. L.; Manthosi, N. L. (International Conference on Public Administration and Development Alternatives (IPADA), 2017)
While the Constitution of the Republic of South Africa (RSA) (Act 108/1996) permits the shift of functions from one sphere of government to another, the reality has been that the two (2) top spheres (provincial and national) are not ready to defer their constitutional obligations to municipalities. This is, attributed to the power that accompanies functions and the ‛lack of adequate capacity’ at local government level. Local government as a sphere closest to communities finds it hard to deliver as expected due to lack of Constitutional mandate to implement on some functions. The housing function is one of the examples of the functional areas of concurrent national and provincial legislative competence listed under Schedule 4 Part A of the RSA Constitution. The Constitution provides for assignment of such function towards their shift from national and provincial sphere to local sphere if those functions would be administered effectively in municipalities and also if municipalities have amassed requisite capacity for administering those functions. The assignment that is envisaged herewith forms part of the subject of decentralisation which is a global debate. In pursuit of decentralisation, local governments should be strengthened towards delivery of social services to citizens. Some of the challenges around decentralisation are highlighted in order to understand the concomitant difficulties that governments are faced with whenever attempts to implement the idea are set in motion. This paper considers the Constitution as well as other pertinent pieces of legislation around powers and functions as distributed across spheres of government; as well as processes of transferring/shifting of those functions. The ensuing paper uses the theory of decentralisation in order to gain understanding of the drive behind empowering local government for improved delivery as well as meeting government targets. Recommendations around the issues of decentralisation as well as shift of powers and functions across spheres of government are made in possible amelioration of identified decentralisation and service delivery bottlenecks.
Journal article
Keywords: Decentralisation; Capacity; Local government; Accreditation; Assignment; Delegation; Powers; Functions; Decentralization in government -- South Africa; Local government -- South Africa; Municipal government